(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
Bandages and stockings are used in a wide variety of ways to provide pressure in medical application; bandages are used to compress part of the leg while a stocking is used to compress the whole leg. The proper use of a bandage or stocking depends on the healthcare setting. To understand the compression effects of bandages and stockings, the pressure of a bandage was compared with that of a stocking made under the same design conditions using Lycra yarn (4.4 Tex, type: T-127c). Multiple-regression analysis was carried out to clarify the factors affecting clothing pressure. The bandage/stocking clothing pressures were explained by the same three factors (i.e., the stretching rates across the width and along circumference and the radius curvature). The relation between stocking pressure (Y) and bandage pressure (x) was linear; Y = 0.89x (R2= 0.984). The pressure of a stocking needs to be 11% greater than that of a bandage to achieve the same effect.